Enhancing the Reading Culture in Ghana: Key Strategies to National Development - Dedzoe-Dzokoto Plockey, Florence (Ghana Library Journal, 2012)
The inculcation of a Reading culture is the process of building up positive reading attitudes. When young people habitually and regularly engage in reading books and other information bearing materials that are not necessarily requiredfor their advancement in their disciplines or careers, they can be said to have inculcated a meaningful reading culture. Being able to read and write opens doors to a variety of human benefits including improved health and nutrition behaviours, political participation, agricultural knowledge, self-confidence, and access to bank accounts. However. most Ghanaian youth of today are waxing stronger with less attraction to books and serious reading. They rather prefer to surf the lnternet, watch TV; party, cohabilate, visiting pubs etc. This paper through a review of the literature, explores several options for promoting the reading habit in Ghana.